Difference in fatigue cracking behaviors of Cu bicrystals with the same component grains but different twin boundaries. (15th January 2015) - Li, L.L.; Zhang, Z.J.; Zhang, P.; Yang, J.B.; Zhang, Z.F.
Abstract : Two Cu bicrystals with identical component grains involved in twinning relationship but different boundaries were cyclically deformed. The results reveal that the coherent twin boundary (CTB) strongly resists fatigue cracking while the incoherent twin boundary (ITB) is intrinsically prone to nucleate fatigue cracks. It is suggested that the same dislocation motions interacting with the ITB and CTB in different ways is the fundamental reason for the distinct fatigue cracking behaviors.